The Influence of Emotion Regulation and Social- Ecological Influence on Suicidality Among Filipino Youth - Lazaro, Rosdy; Castillo, Sheryll Ann (12th International Scholars Conference 2025, 2026)
Suicide remains a leading cause of death for adolescents and young adults worldwide, and recent surveillance reports show a worrisome uptick in self-harm among Filipino youth despite national mental-health legislation. Grounded in the dual-process model of emotion regulation and Bronfenbrenner’s ecological theory, this descriptive correlational study investigated how emotion regulation (ER) strategies and social ecologicalinfluences (SEI) relate to suicidality (SUI) in a sample of 653 students randomly selected from four state universities in CALABARZON, Philippines. Participants reported generally high cognitive reappraisal (M = 3.98, SD = 0.57) and perceived social support (M = 3.89, SD = 0.77) alongside low suicide ideation (M = 1.71, SD = 0.75) and hopelessness (M = 2.02, SD = 0.49). Pearson correlations showed that overall ER (r = –.379, p < .001) and SEI (r = –.342, p < .001) were inversely associated with suicidality, whereas emotional suppression correlated positively (r = .205, p <.001). ANOVA revealed that current mental-health problems (p < .001) and gender (p < .01) significantly elevated SUI, but age and socioeconomic status did not. In multiple regression, emotional suppression emerged as a risk factor (β = .135, p < .001), while cognitive reappraisal (β = –.113, p = .001) and family support (β = –.303, p < .001) predicted lower suicidality. The findings validate the proposed integrative framework linking ER and SEI to SUI and underscore the protective value of adaptive regulation and strong familial ties. Implications include prioritizing family-centered, culturally congruent interventions that teach cognitive reappraisal and enhance social support networks in school-based counseling and community mental-health programs, thereby equipping Filipino youth with person-specific resources tocounter suicidality.